Analysis and control of a unified power flow controller system - Zhu, Xin. (2009)
The Unified Power Flow Controller (UPFC)modeled in the synchronous reference frame is investigated in this thesis for the control of power flow in a transmission system. An AC voltage vector generated by a GTO-based inverter is injected in series with the phase voltage in the transmission line to control real and reactive power flow. The mathematical model of UPFC is built, and a robust H^ controller is proposed to regulate line currents in both the shunt and series inverters of the UPFC. The controller ensures robust performance and internal stability of the UPFC against power system disturbances and unstructured parameter variations. Conventional PI control system performance is compared with that based on the proposed scheme to highlight excellent robustness features in the new scheme.